Insurgency and counterinsurgency a global history - Black, Jeremy (Rowman & Littlefield, 2016)
"A world history of insurgencies and of counterinsurgency warfare. Jeremy Black moves beyond the conventional Western-centric narrative, reaching back to antiquity to trace the pre-modern origins of war within states."--Provided by publisher